Pectoralis minor index range of healthy 18–24-year-old students from a Kenyan public university - Eugene C. Agweyu; Joseph M. Matheri; Benita Olivier; Elzette Korkie (South African Journal of Physiotherapy)
Background: The pectoralis minor muscle (PMM) length is critical for shoulder movement and stability, often implicated in dysfunction and pain. The pectoralis minor index (PMI) quantifies this muscle’s length relative to body dimensions. Typical PMI values range from 10.0 cm to 12.5 cm in healthy adults, with data for Kenyan populations.